Mapping and Determining of Priority Areas Interventions for Toddler Diarrhea in Surabaya - Yuli Puspita Devi; Sofwatun Nida; Muthmainnah Muthmainnah; Martya Rahmaniati Makful (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2022)
Diarrhea is still the second leading cause of death in toddlers besides pneumonia. The highest number of cases of diarrhea in toddlers in East Java is Surabaya. This study aimed to describe the distribution of toddler diarrhea based on risk factors using a regional mapping approach in Surabaya. This study was an ecological study with a regional mapping approach. The independent variables used as risk factors for toddler diarrhea were healthy latrines, drinking water facilities, open defecation free (ODF), and complete basic immunizations. The unit of analysis used was the districts that were processed from the Surabaya Health Profile data in 2019. Results showed most cases of diarrhea under five occurred in Wonokromo, Sawahan, Tambak Sari, and Kenjeran District. There was a significant relationship between toddler diarrhea with complete basic immunization (p = 0.008), while the relationship with healthy latrines, ODF, and drinking water sanitation was not significant. This study concluded that 8 of 31 districts were prioritized for handling toddler diarrhea in Surabaya. In addition, there is a need for dissemination to the community through optimizing the role of health workers at the Puskesmas regarding complete basic relationships and the incidence of diarrhea in toddlers.